Multi-Scale Modeling and Numerical Simulation for CVI Process (Communications in Computational Physics, 2010)
We consider the multi-scale modeling of the isothermal chemical vapor infiltration(CVI) process for the fabrication of C/SiC composites. We first present a microscopicmodel in which the preform is regarded as a two-phase porous media describedby a dynamic pore-scale node-bond network during the fabrication process. We thendevelop a macroscopic model by a upscaling procedure based on the homogenizationtheory.